Comparison of transdermal diclofenac patch with oral diclofenac as an analgesic modality following multiple premolar extractions in orthodontic patients: A cross over efficacy trial - Bhaskar, Hemant (Medknow Publications Pvt Ltd, 2010)
AIMS: This study was performed to compare the degree of post operative analgesia, patient compliance, and frequency of adverse events with the use of oral diclofenac tablets and transdermal diclofenac patch following multiple premolar extractions in patients undergoing orthodontic treatment. MATERIALS AND METHODS: Twenty young pre-orthodontic patients requiring bilateral maxillary and mandibular first premolar extractions were selected for the study. The right maxillary and mandibular first premolars were extracted first and 50 mg oral diclofenac sodium tablets were prescribed to be taken thrice a day for three days. In the next appointment, the contralateral first premolars were extracted and a 100 mg transdermal diclofenac patch was applied once a day for three days. Pain relief and pain intensity with both the diclofenac formulations was recorded for each of the three postoperative days using 5-point Verbal Pain Intensity and Pain Relief Score Charts. RESULTS AND CONCLUSIONS: Statistical analyses revealed that there was a gradual increase in pain relief scores and a gradual decrease in pain intensity scores with the use of oral diclofenac tablets as well as with the transdermal patch. However, subjects reported that they were more comfortable using the transdermal patch particularly due to the once-a-day application and lesser frequency of systemic adverse effects. Results of this study indicate that the transdermal diclofenac patch provides as potent analgesia as the oral diclofenac tablets with the added advantage of better patient compliance and may be used for routine post extraction analgesia.